HISTOLOGICAL SPECTRUM OF PREMALIGNANT AND PREINVASIVE MALIGNANT LESIONS IN CYTOLOGICALLY AND RADIOLOGICALLY DIAGNOSED BENIGN BREAST LESIONS-OUR EXPERIENCE IN A TERTIARY CARE HOSPITAL - MUSFIQUE, JABIN; TALUKDAR, LEENA; BARMAN, MANOJ (International Journal of Current Pharmaceutical Research, 2023)
Objective: The aim of this study is to detect precancerous lesions and intraductal (in situ) malignancies in cytologically and radiologically diagnosed benign breast lesions and its prevalence in different age groups. Methods: A total of 448 cases of breast lumps were diagnosed cytological as benign breast lesions in our cytology division from july 2022 to june 2023. Of these, 148 cases were available for histopathological examination. Results: On Histopathology, 122 cases (82.4%) were diagnosed as benign lesions. 19 (12.8%) cases were found to harbour pre-malignant lesions, 06 (4.0%) cases as in-situ carcinomas and 1 (0.6%) case of encapsulated papillary carcinoma without invasion. Conclusion: To conclude, prevention of development of carcinoma of breast is the key step to reduce the burden of morbidity and mortality. Recognising pre-malignant lesions can go a long way in reducing development of invasive carcinoma, for which histopathological examination is the most helpful tool. Thus any benign breast lesions that have been detected to harbour pre-malignant changes must be placed into a separate group than from purely benign breast lesions. These groups must be followed up and treated according to standard available protocols.